Lithium-rich manganese-based core-shell material as well as preparation method and application thereof
By using phase structure gradient and phosphate coverage technology in lithium-rich manganese-based positive electrode materials, the problem of degradation of material circulation stability is solved, and high energy density and excellent cycling performance are achieved.
Patent Information
- Application Number
- CN202510132629.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-06
AI Technical Summary
Lithium-rich manganese-based positive electrode material has reduced cycle stability due to interface reaction and oxygen release problems in lithium-ion batteries, which limits its commercial application.
A phase structure gradient lithium-manganese-based material is used as the core, and the surface is covered with phosphate, and the shell is combined to form a gradient structure to improve the electrochemical performance of the material.
The cycle stability, discharge specific capacity and safety performance of lithium-rich manganese-based core-shell materials are significantly improved, and the electrochemical performance requirements of lithium-ion batteries are met.
Smart Images

Figure CN119905567A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and particularly relates to a lithium-rich manganese-based core-shell material, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high power, small size, and good cycle performance. However, with the development of electronic technology and electric vehicles, higher requirements are put forward for the performance of lithium-ion batteries. As an important component of lithium-ion batteries, the cathode material is closely related to the energy density of lithium-ion batteries. Lithium-rich manganese-based cathode materials are regarded as promising cathode materials due to their low cost and specific capacity higher than 300 mAhg -1 , high energy density. However, the interfacial reaction between the lithium-rich manganese-based cathode material and the electrolyte, as well as the problem of oxygen release under high voltage, lead to the decline of the cycle stability of this material, thereby limiting the commercial application of lithium-rich manganese-based cathode materials.
[0003] Among the many modification methods of lithium-rich manganese-based cathode materials, surface coating of lithium-rich manganese-based cathode materials can effectively alleviate the lack of lattice oxygen on the surface of lithium-rich manganese-based cathode materials and the interfacial reaction between electrode materials. The coating layer physically isolates the cathode material and the electrolyte, inhibits the release of lattice oxygen on the surface of lithium-rich manganese-based cathode materials, and prevents side reactions between high-valent metal cations and reactive oxygen species on the material surface and the electrolyte. However, the first-cycle performance of the modified lithium-rich manganese-based cathode material is poor, and the overall electrochemical performance is not good. Summary of the Invention
[0004] The purpose of the present invention is to provide a lithium-rich manganese-based core-shell material, a preparation method thereof, and an application thereof. The lithium-rich manganese-based core-shell material provided by the present invention has excellent electrochemical performance.
[0005] In order to achieve the above purpose, the present invention provides the following technical solutions:
[0006] The present invention provides a lithium-rich manganese-based core-shell material, including a phase-structure gradient lithium-rich manganese-based material and a shell covering the surface of the phase-structure gradient lithium-rich manganese-based material; the general formula of the phase-structure gradient lithium-rich manganese-based material is xLi2MnO3·(1 - x)LiTMO2 - yLi2MnO3·(1 - y)LiTMO2, 0 < y < x < 1, where TM is one or more of Ni, Co, and Mn; the surface layer of the phase-structure gradient lithium-rich manganese-based material is infiltrated with phosphate; the shell includes Li3P 1+a O4S 4a , 0 ≤ a ≤ 1.
[0007] Preferably, the phase structure gradient lithium-manganese-rich based material includes a monoclinic Li2MnO3 phase and a rhombic LiTMO2 phase; the content of the monoclinic Li2MnO3 phase decreases from the inside to the outside; and the content of the rhombic LiTMO2 phase increases from the inside to the outside.
[0008] Preferably, the content of the monoclinic Li2MnO3 phase decreases linearly from the inside to the outside; and the content of the rhombohedral LiTMO2 phase increases linearly from the inside to the outside.
[0009] Preferably, the phosphate is lithium phosphate; the mass ratio of the phosphate to the phase structure gradient lithium-rich manganese-based material is 0.1 to 5:100.
[0010] Preferably, the content of S in the shell increases from the inside to the outside.
[0011] Preferably, the mass ratio of the phase structure gradient lithium-rich manganese-based material to the shell is 1000:5-20.
[0012] Preferably, the lithium-rich manganese-based core-shell material is spherical in shape, with a particle size of 0.5 to 20 μm.
[0013] The present invention also provides a method for preparing the lithium-rich manganese-based core-shell material described in the above scheme, comprising the following steps:
[0014] (1) mixing a phase structure gradient lithium-rich manganese-based material, a lithium source, a phosphorus source and a complexing agent, performing a complexing reaction and then sintering to obtain a preliminary lithium-rich manganese-based material;
[0015] (2) the preliminary lithium-rich manganese-based material, P4S 16 The mixture is mixed with an ether solvent and then dried to obtain the lithium-rich manganese-based core-shell material.
[0016] Preferably, the sintering temperature is 200-600° C., and the sintering time is 2-7 hours.
[0017] The present invention also provides the application of the lithium-rich manganese-based core-shell material described in the above scheme or the lithium-rich manganese-based core-shell material obtained by the preparation method described in the above scheme in the field of lithium-ion batteries.
[0018] The present invention provides a lithium-rich manganese-based core-shell material. The present invention uses a phase structure gradient lithium-rich manganese-based material as the core, regulates the phase structure gradient, and coats the surface of the phase structure gradient lithium-rich manganese-based material with phosphate, and cooperates with the shell to obtain a high energy density lithium-rich manganese-based core-shell material, while having excellent cycle stability, discharge specific capacity and safety performance.
[0019] By coating the phase structure gradient lithium-rich manganese-based material with phosphate, part of the phosphate ions are doped into the surface layer of the phase structure gradient lithium-rich manganese-based material, combining with more rhombic LiTMO2 phases in the surface layer, forming stronger binding bond energies between transition metal cations (Ni, Co, Mn) and polyanionic phosphates, thereby further improving the energy density of the lithium-rich manganese-based core-shell material and having a high capacity retention rate. By coating the inner core with an outer shell and setting a gradient, the lithium ions are transported stably and rapidly, and the transformation from layered to spinel-like caused by structural degradation is significantly reduced, thereby improving the cycle stability of the lithium-rich manganese-based core-shell material.
[0020] The present invention also provides a preparation method of the lithium-rich manganese-based core-shell material described in the above solution. The preparation method provided by the present invention has simple steps, convenient operation, low cost, and is suitable for industrial production.
[0021] The present invention also provides an application of the lithium-rich manganese-based core-shell material described in the above solution or the lithium-rich manganese-based core-shell material obtained by the preparation method described in the above solution in the field of lithium-ion batteries. The lithium-rich manganese-based core-shell material provided by the present invention has a high energy density, a high capacity retention rate, and good cycle performance, can meet the electrochemical performance requirements of lithium-ion batteries, is suitable as a battery cathode material, and has broad application prospects. Brief Description of the Drawings
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0023] Figure 1 It is a schematic diagram of the lithium-rich manganese-based core-shell material prepared in Example 1 of the present invention. Detailed Embodiments
[0024] The present invention provides a lithium-rich manganese-based core-shell material, including a phase structure gradient lithium-rich manganese-based material and an outer shell coated on the surface of the phase structure gradient lithium-rich manganese-based material; the general formula of the phase structure gradient lithium-rich manganese-based material is xLi2MnO3·(1 - x)LiTMO2 - yLi2MnO3·(1 - y)LiTMO2, 0 < y < x < 1, where TM is one or more of Ni, Co, and Mn; the surface layer of the phase structure gradient lithium-rich manganese-based material is infiltrated with phosphate; the outer shell includes Li3P 1+a O4S 4a , 0 ≤ a ≤ 1.
[0025] The lithium-rich manganese-based core-shell material provided by the present invention includes a phase-structure gradient lithium-rich manganese-based material; the general formula of the phase-structure gradient lithium-rich manganese-based material is xLi2MnO3·(1-x)LiTMO2 (core center) - yLi2MnO3·(1-y)LiTMO2 (core surface layer), 0 < y < x < 1, where TM is one or more of Ni, Co, and Mn; the phase-structure gradient lithium-rich manganese-based material includes a monoclinic Li2MnO3 phase and a rhombohedral LiTMO2 phase; the content of the monoclinic Li2MnO3 phase preferably decreases sequentially from the inside to the outside, more preferably linearly decreases from the inside to the outside; the content of the rhombohedral LiTMO2 phase preferably increases sequentially from the inside to the outside, more preferably linearly increases from the inside to the outside. By adjusting the ratio of the monoclinic Li2MnO3 and the rhombohedral LiTMO2 from the inside to the outside as described above, the present invention improves the electrochemical properties such as the cycle stability, discharge specific capacity, and safety performance of the lithium-rich manganese-based core-shell material in a lithium-ion battery.
[0026] In the present invention, the phosphate is preferably lithium phosphate; the mass ratio of the phosphate to the phase-structure gradient lithium-rich manganese-based material is preferably 0.1-5:100, specifically it can be 0.1:100, 0.2:100, 0.3:100, 0.5:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, or 5:100. By controlling the content of the phosphate, the thickness of the outer shell is adjusted during the preparation process. Through the setting of the phosphate, a small amount of phosphate ions are doped into the interior of the phase-structure gradient lithium-rich manganese-based material. Due to the strong binding bond energy between the phosphate polyanion and the transition metal cation (especially Ni), the energy density of the phase-structure gradient lithium-rich manganese-based material is increased; the doping of the phosphate polyanion will enhance the binding bond energy between the cations of Ni and Co and the anions, and has almost no influence on the oxidation state of the Mn cation. Since the content of Co and Ni on the surface of the phase-structure gradient lithium-rich manganese-based material of the present invention is high and the content of Mn is reduced, the binding bond energy between the phosphate polyanion and the transition metal will be greatly improved.
[0027] The lithium-rich manganese-based core-shell material provided by the present invention includes an outer shell; the Li3P 1+a O4S 4a represents the reaction product of P4S 16 with the phosphate, where the content of S changes in a gradient, that is, the content of the thiophosphate changes in a gradient.
[0028] In the present invention, the content of S in the shell preferably increases from the inside to the outside, more preferably increases linearly from the inside to the outside. The shell of the present invention is a gradient structure, through which lithium ions can be transported stably and quickly, and the transition from layered to spinel caused by structural degradation is significantly reduced, thereby improving the cycle stability of the material.
[0029] In the present invention, the value of a can be preferably 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.
[0030] In the present invention, the mass ratio of the phase structure gradient lithium-rich manganese-based material to the shell is preferably 1000:5-20, specifically 1000:5, 1000:8, 1000:10, 1000:12, 1000:15, 1000:17 or 1000:20.
[0031] In the present invention, the lithium-rich manganese-based core-shell material is preferably spherical in shape, and the particle size is preferably 0.5 to 20 μm, specifically 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm or 20 μm.
[0032] The present invention also provides a method for preparing the lithium-rich manganese-based core-shell material described in the above scheme, comprising the following steps:
[0033] (1) mixing a phase structure gradient lithium-rich manganese-based material, a lithium source, a phosphorus source and a complexing agent, performing a complexing reaction and then sintering to obtain a preliminary lithium-rich manganese-based material;
[0034] (2) the preliminary lithium-rich manganese-based material, P4S 16 The mixture is mixed with an ether solvent and then dried to obtain the lithium-rich manganese-based core-shell material.
[0035] The present invention mixes a phase structure gradient lithium-rich manganese-based material, a lithium source, a phosphorus source and a complexing agent (referred to as mixed A) for complexing reaction and then sintering to obtain a preliminary lithium-rich manganese-based material. The present invention wet-coates phosphate so that a small amount of phosphate is doped into the surface layer of the phase structure gradient lithium-rich manganese-based material. Due to the strong binding energy between the phosphate polyanion and the transition metal cation, the energy density of the material is increased, the lithium ion transmission performance is improved, and the phosphate is evenly coated, which reduces the side reactions of the material and the electrolyte to a certain extent.
[0036] In the present invention, the lithium source preferably includes one or more of lithium hydroxide and lithium salt; the lithium hydroxide is preferably lithium hydroxide; the lithium salt preferably includes one or more of lithium chloride, lithium acetate and lithium nitrate; the lithium source is more preferably lithium hydroxide and lithium nitrate.
[0037] In the present invention, the phosphorus source is preferably phosphoric acid.
[0038] In the present invention, the molar ratio of the lithium source to the phosphorus source is preferably 2 to 4: 1, specifically 2: 1, 2.2: 1, 2.5: 1, 2.7: 1, 3: 1, 3.2: 1, 3.5: 1, 3.7: 1 or 4: 1. The present invention adjusts the final content of phosphate by controlling the above content.
[0039] In the present invention, the complexing agent is preferably an inorganic acid; the inorganic acid is preferably citric acid. Under the action of the complexing agent, lithium ions and phosphate ions are complexed on the surface of the phase structure gradient lithium-rich manganese-based material, and then sintered to form phosphate.
[0040] In the present invention, the molar ratio of the complexing agent to the phosphorus source is preferably 2 to 4:1, specifically 2:1, 2.2:1, 2.5:1, 2.7:1, 3:1, 3.2:1, 3.5:1, 3.7:1 or 4:1. The present invention adjusts the final content of phosphate by controlling the above content.
[0041] In the present invention, the mixing A is preferably: a lithium source, a complexing agent and a phosphorus source are first mixed to obtain a phosphorus-containing solution, and the phosphorus-containing solution and a phase structure gradient lithium-rich manganese-based material are second mixed; the time for the first mixing is preferably 0.5 to 5 hours, specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours; the time for the second mixing is preferably 0.5 to 2 hours, specifically 0.5 hours, 1 hour, 1.5 hours or 2 hours.
[0042] In the present invention, the temperature of the complexing reaction is preferably room temperature, and the reaction time is the total time of the mixing A.
[0043] In the present invention, after the complexation reaction, preferably the obtained product is separated from solid and liquid; the solid-liquid separation is preferably filtered; after the solid-liquid separation, preferably the obtained solid is dried; the drying is preferably oven drying.
[0044] In the present invention, the sintering temperature is preferably 200-600°C, specifically 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, and the heat preservation sintering time is preferably 2-7h, specifically 2h, 3h, 4h, 5h, 6h or 7h. The present invention promotes the combination of lithium ions and phosphates to form phosphates through sintering, and the obtained preliminary lithium-rich manganese-based material is a phosphate-coated phase structure gradient lithium-rich manganese-based material.
[0045] After obtaining the preliminary lithium-rich manganese-based material, the present invention combines the preliminary lithium-rich manganese-based material, P4S 16and ether solvent (referred to as mixed B) and then dried to obtain the lithium-rich manganese-based core-shell material. The present invention adopts an in-situ solution method to prepare the shell. 16 The electrical conductivity of sulfur-rich solution and P4S 16 SS bridge bond in molecular structure, P4S 16 and lithium phosphate have -40meVatom -1 Negative reaction energy, P4S 16 It will cause lithium phosphate to sulfide and form Li3P 1+a O4S 4a .
[0046] In the present invention, the preliminary lithium-rich manganese-based material and P4S 16 The mass ratio of S is preferably 1000:5-20, specifically 1000:5, 1000:7, 1000:9, 1000:10, 1000:12, 1000:15, 1000:17 or 1000:20. The present invention adjusts the content of S in the shell by controlling the above amount, thereby regulating the electrochemical properties of the lithium-rich manganese-based core-shell material.
[0047] In the present invention, the ether solvent is preferably diethylene glycol dimethyl ether.
[0048] In the present invention, the mixture B is preferably: the preliminary lithium-rich manganese-based material and P4S 16 The solution was mixed third.
[0049] In the present invention, the P4S 16 The concentration of the solution is preferably 5 to 20 mg / mL, specifically 5 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 14 mg / mL, 16 mg / mL, 18 mg / mL or 20 mg / mL. 16 The concentration of the solution affects the content of S in the shell, P4S 16 The higher the concentration of the solution, the higher the S content in the shell.
[0050] In the present invention, the temperature of the third mixing is preferably room temperature; the time of the third mixing is preferably 1 to 3 hours, specifically 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0051] In the present invention, the drying temperature is preferably 60-100°C, specifically 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, and the heat preservation and drying time is preferably 1-3h, specifically 1h, 1.5h, 2h, 2.5h or 3h.
[0052] The present invention also provides the application of the lithium-rich manganese-based core-shell material described in the above scheme or the lithium-rich manganese-based core-shell material obtained by the preparation method described in the above scheme in the field of lithium-ion batteries.
[0053] The lithium-rich manganese-based core-shell material provided by the present invention has high energy density and good cycle performance, can meet the electrochemical performance requirements of lithium-ion batteries, and has broad application prospects.
[0054] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0055] Example 1
[0056] This example prepares a lithium-rich manganese-based core-shell material with a structure such as Figure 1 As shown; the core of the lithium-rich manganese-based core-shell material is a phase structure gradient lithium-rich manganese-based material, and the chemical composition of the particle center of the phase structure gradient lithium-rich manganese-based material is 0.5Li2MnO3·0.5Li(Ni 0.42 Mn 0.42 Co 0.16 )O2, the chemical composition of the particle surface is 0.3Li2MnO3·0.7Li(Ni 0.42 Mn 0.42 Co 0.16 )O2; the shell of the lithium-rich manganese-based core-shell material includes Li3P 1+a O4S 4a , 0≤a≤1, the value of a gradually increases from the inside to the outside of the shell.
[0057] The preparation method of the lithium-rich manganese-based core-shell material in this embodiment includes the following steps:
[0058] (1) mixing lithium hydroxide, citric acid and phosphoric acid in a molar ratio of 3:3:1 for 3 hours, adding a phase structure gradient lithium-rich manganese-based material, mixing, filtering and drying in sequence, and then sintering at 400° C. for 4.5 hours to obtain a preliminary lithium-rich manganese-based material;
[0059] (2) The preliminary lithium-rich manganese-based material and the P4S with a concentration of 12 mg / mL were mixed. 16 Solution (solvent is diethylene glycol dimethyl ether, solute is P4S 16 powder) for 2 hours and then dried at 80° C. for 2 hours to obtain the lithium-rich manganese-based core-shell material; wherein the preliminary lithium-rich manganese-based material and P4S 16 The mass ratio of the powders is 1:0.01.
[0060] The method for preparing the phase structure gradient lithium-rich manganese-based material comprises the following steps:
[0061] (a) nickel sulfate (NiSO4·6H2O), cobalt sulfate (NiSO4·7H2O) and manganese sulfate (MnSO4·H2O) were dissolved in deionized water to prepare solution A and solution B with a total sulfate concentration of 2 mol / L, respectively, wherein the molar ratio of Ni, Co and Mn in solution A was 0.21:0.08:0.71, and the molar ratio of Ni, Co and Mn in solution B was 0.343:0.1305:0.5265; at the same time, 2 mol / L Na2CO3 solution and 0.2 mol / L ammonia solution were prepared;
[0062] (b) adding 600 mL of solution B prepared in step (a) into 600 mL of solution A in a stirring state through a constant flow pump, and at the same time, adding the mixed salt solution obtained by mixing solution A and solution B into the reactor through a constant flow pump, and adding Na2CO3 solution and ammonia water into the reactor in parallel through constant flow pumps, respectively, controlling the stirring speed to 1000 rpm, adjusting the pH value to 8.1, and coprecipitating at 55°C for 10 hours to obtain a phase structure gradient lithium-rich manganese-based material precursor;
[0063] (c) The phase structure gradient lithium-rich manganese-based material precursor prepared in step (b) is filtered, washed and dried in sequence, and evenly mixed with Li2CO3 in a ratio of 1.6:1 between the molar number of Li and the total molar number of Ni, Co and Mn, and pre-calcined at 500°C in an air atmosphere for 5 h, and then heated to 900°C and kept warm for 10 h to obtain a phase structure gradient lithium-rich manganese-based material.
[0064] Example 2
[0065] In this embodiment, a lithium-rich manganese-based core-shell material is prepared. The core of the lithium-rich manganese-based core-shell material is a phase structure gradient lithium-rich manganese-based material. The chemical composition of the particle center of the phase structure gradient lithium-rich manganese-based material is 0.5Li2MnO3·0.5Li(Ni 0.42 Mn 0.42 Co 0.16 )O2, the chemical composition of the particle surface is 0.3Li2MnO3·0.7Li(Ni 0.42 Mn 0.42 Co 0.16 )O2; the outer shell includes Li3P 1+a O4S 4a , 0≤a≤1, the value of a gradually increases from the inside to the outside of the shell.
[0066] The preparation method of the lithium-rich manganese-based core-shell material in this embodiment includes the following steps:
[0067] (1) After mixing lithium acetate, citric acid and phosphoric acid in a molar ratio of 2:2:1 for 0.5 h, adding a phase structure gradient lithium-rich manganese-based material, mixing, filtering and drying in sequence, and then sintering at 200° C. for 7 h to obtain a preliminary lithium-rich manganese-based material; the preparation method of the phase structure gradient lithium-rich manganese-based material is the same as that of Example 1;
[0068] (2) The preliminary lithium-rich manganese-based material and the P4S with a concentration of 5 mg / mL described in step (1) are mixed with 16 Solution (solvent is diethylene glycol dimethyl ether, solute is P4S 16 powder) was mixed for 1 hour and then dried at 60° C. for 3 hours to obtain the lithium-rich manganese-based core-shell material; wherein the preliminary lithium-rich manganese-based material and P4S 16 The mass ratio of the powder is 1:0.005.
[0069] Example 3
[0070] In this embodiment, a lithium-rich manganese-based core-shell material is prepared. The core of the lithium-rich manganese-based core-shell material is a phase structure gradient lithium-rich manganese-based material. The chemical composition of the particle center of the phase structure gradient lithium-rich manganese-based material is 0.5Li2MnO3·0.5Li(Ni 0.42 Mn 0.42 Co 0.16 )O2, the chemical composition of the particle surface is 0.3Li2MnO3·0.7Li(Ni 0.42 Mn 0.42 Co 0.16 )O2; the outer shell includes Li3P 1+a O4S 4a , 0≤a≤1, the value of a gradually increases from the inside to the outside of the shell.
[0071] The preparation method of the lithium-rich manganese-based core-shell material in this embodiment includes the following steps:
[0072] (1) After mixing lithium nitrate, citric acid and phosphoric acid in a molar ratio of 4:4:1 for 5 hours, adding a phase structure gradient lithium-rich manganese-based material, mixing, filtering and drying in sequence, and then sintering at 600° C. for 2 hours to obtain a preliminary lithium-rich manganese-based material; the preparation method of the phase structure gradient lithium-rich manganese-based material is the same as that of Example 1;
[0073] (2) The preliminary lithium-rich manganese-based material and the P4S with a concentration of 20 mg / mL in step (1) are mixed. 16 Solution (solvent is diethylene glycol dimethyl ether, solute is P4S 16 powder) for 3 hours and then dried at 100° C. for 3 hours to obtain the lithium-rich manganese-based core-shell material; wherein the preliminary lithium-rich manganese-based material and P4S 16 The mass ratio of the powders is 1:0.02.
[0074] Example 4
[0075] The preparation method of this embodiment is the same as that of embodiment 1, except that: the preliminary lithium-rich manganese-based material and P4S 16 The mass ratio of the powder was changed from 1:0.01 to 1:0.05.
[0076] Example 5
[0077] The preparation method of this embodiment is the same as that of embodiment 1, except that: the preliminary lithium-rich manganese-based material and P4S 16 The mass ratio of the powder was changed from 1:0.01 to 1:0.001.
[0078] Comparative Example 1
[0079] The preparation method of this comparative example is the same as that of Example 1, except that: the step (2) P4S 16 The solution was replaced with P2S5 solution.
[0080] Comparative Example 2
[0081] The preparation method of this comparative example is the same as that of Example 1, except that: this comparative example does not perform step (2), and only a layer of lithium phosphate is coated on the surface of the phase structure gradient lithium-rich manganese-based material.
[0082] Comparative Example 3
[0083] The preparation method of this comparative example is the same as that of Example 1, except that the phase structure gradient lithium-manganese-rich based material is replaced by a layered lithium-manganese-rich based material without phase structure gradient change, and the molar ratio of nickel, cobalt and manganese in the lithium-manganese-rich based material remains unchanged.
[0084] Comparative Example 4
[0085] The preparation method of this comparative example is the same as that of Example 1, except that: this comparative example directly uses the phase structure gradient lithium-rich manganese-based material as the target product, that is, it is not modified.
[0086] Test Example 1
[0087] The electrochemical properties of the lithium-rich manganese-based core-shell materials of Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the electrochemical properties tests included tests of cycle performance and average voltage decay, wherein the cycle performance test method was as follows: at room temperature (25°C), the battery was activated for 3 cycles at a voltage range of 2.0 to 4.8 V and a current density of 0.1 C, and then the charge and discharge cycle test was performed at a voltage range of 2.0 to 4.8 V and a current density of 0.1 C, and the capacity retention rate within 100 cycles was tested; the test conditions for the average voltage decay were 3.61 V to 3.45 V, and the results are shown in Table 1.
[0088] Table 1 Electrochemical properties of lithium-rich manganese-based core-shell materials of Examples 1 to 5 and Comparative Examples 1 to 4
[0089] Average voltage decay Capacity retention rate Example 1 0.55mV / cycle 98.8% Example 2 0.57mV / cycle 98.4% Example 3 0.56mV / cycle 98.6% Example 4 0.68mV / cycle 96.2% Example 5 0.72mV / cycle 95.4% Comparative Example 1 0.78mV / cycle 93.1% Comparative Example 2 0.79mV / cycle 94.5% Comparative Example 3 1.50mV / cycle 85.1% Comparative Example 4 0.81mV / cycle 92.2%
[0090] It can be seen from Table 1 that the lithium-rich manganese-based core-shell material prepared by the present invention has a low voltage drop and a high cycle stability; it can be seen from Examples 4 to 5 that the preliminary lithium-rich manganese-based material and P4S 16 If the mass ratio of the powder is too high or too low, the cycle stability of the lithium-rich manganese-based core-shell material will decrease; as shown in Comparative Example 1, 16 The solution is replaced by P2S5 solution, and the sulfur loading process cannot occur. Therefore, no thiophosphate is produced, and the cycle stability of the battery is reduced. It can be seen from Comparative Example 2 that only lithium phosphate is coated on the surface of the lithium-rich manganese-based material, and the cycle performance of the battery is not significantly improved. It can be seen from Comparative Example 3 that instead of using a lithium-rich manganese-based material with a phase structure gradient as the inner core, a lithium-rich manganese-based material without a phase structure gradient change is used, and the cycle stability of the battery is reduced. It can be seen from Comparative Example 4 that directly using a lithium-rich manganese-based material with a phase structure gradient as the target product has an electrochemical cycle stability significantly lower than that of the lithium-rich manganese-based core-shell materials in Examples 1 to 3 of the present invention.
[0091] It can be seen from the above embodiments that the lithium-rich manganese-based core-shell material provided by the present invention has a high capacity retention rate and excellent cycle stability.
[0092] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A lithium-rich manganese-based core-shell material, characterized in that: It includes a phase structure gradient rich lithium manganese-based material and a shell covering the surface of the phase structure gradient rich lithium manganese-based material; the general formula of the phase structure gradient rich lithium manganese-based material is xLi2MnO3·(1-x)LiTMO2-yLi2MnO3·(1-y)LiTMO2, where 0 < y < x < 1, and TM in the formula is one or more of Ni, Co, and Mn; The surface layer of the phase structure gradient rich lithium manganese-based material is infiltrated with phosphate; The shell includes Li3P 1+a O4S 4a , 0≤a≤1.
2. The lithium-rich manganese-based core-shell material according to claim 1, characterized in that The phase structure gradient rich lithium manganese-based material includes a monoclinic Li2MnO3 phase and a rhombohedral LiTMO2 phase; The content of the monoclinic Li2MnO3 phase decreases sequentially from the inside to the outside; The content of the rhombohedral LiTMO2 phase increases sequentially from the inside to the outside.
3. The lithium-rich manganese-based core-shell material according to claim 2, characterized in that: The content of the monoclinic Li2MnO3 phase decreases linearly from the inside to the outside; The content of the rhombohedral LiTMO2 phase increases linearly from the inside to the outside.
4. The lithium-rich manganese-based core-shell material according to claim 1, characterized in that: The phosphate is lithium phosphate; the mass ratio of the phosphate to the phase structure gradient rich lithium manganese-based material is 0.1 - 5:
100.
5. The lithium-rich manganese-based core-shell material according to claim 1 or 2, characterized in that: The content of S in the shell increases sequentially from the inside to the outside.
6. The lithium-rich manganese-based core-shell material according to claim 1, characterized in that: The mass ratio of the phase structure gradient rich lithium manganese-based material to the shell is 1000:5 - 20.
7. The lithium-rich manganese-based core-shell material according to claim 1 or 6, characterized in that: The shape of the rich lithium manganese-based core-shell material is spherical, and the particle size is 0.5 - 20 μm.
8. The method for preparing the lithium-rich manganese-based core-shell material according to any one of claims 1 to 7, characterized in that: It includes the following steps: (1) Mix the phase structure gradient rich lithium manganese-based material, lithium source, phosphorus source, and complexing agent, carry out a complexing reaction and then sinter to obtain a preliminary rich lithium manganese-based material; (2) the preliminary lithium-rich manganese-based material, P4S 16 The mixture is mixed with an ether solvent and then dried to obtain the lithium-rich manganese-based core-shell material.
9. The preparation method according to claim 8, characterized in that: The temperature of the sintering is 200 - 600 °C, and the holding sintering time is 2 - 7 h.
10. Application of the rich lithium manganese-based core-shell material according to any one of claims 1 - 7 or the rich lithium manganese-based core-shell material obtained by the preparation method according to any one of claims 8 - 9 in the field of lithium-ion batteries.
Citation Information
Patent Citations
Dual-domain lithium-rich layered oxide material and preparation method
CN106025256A
Lithium ion battery positive electrode material and preparation method and application thereof
CN114628679A
Active material for battery, manufacturing method of the same, non-aqueous electrolytic battery and battery pack
US20090042095A1
Method for preparing an electrode material and electrochemical use the same
US20240105921A1
Ternary material precursor, ternary positive electrode material, and preparation method therefor and use thereof
WO2024250223A1